Performance Management and Lecturer Performance in Indonesian Higher Education: A SEM-PLS Analysis - Agoes Ganesha Rahyuda; Putu Laksmita Dewi Rahmayanti; Diah Pradnya Dewi (proceedings.icesy, 2026)
Lecturer performance is crucial for improving higher education quality and strengthening the global competitiveness of Indonesian universities. Effective performance management—through clear goals, consistent evaluation, transparent communication, and constructive feedback—supports the fulfillment of the Tri Dharma of higher education. Based on Social Exchange Theory, well-implemented performance management enhances organizational commitment and job satisfaction, which in turn improve lecturer performance. This study investigates a performance management model in Indonesian higher education using a quantitative survey of 280 lecturers. Data were analyzed using SEM-PLS with SmartPLS 4.0. The findings are expected to provide evidence for designing adaptive human resource policies to enhance lecturer performance and institutional quality.